OPTIMALISASI ASAS OPORTUNITAS PADA KEWENANGAN JAKSA GUNA MEMINIMALISIR DAMPAK PRIMUM REMEDIUM DALAM PEMIDANAAN - Nugraha, Yodi (Faculty of Law, Parahyangan Catholic University, 2020)
In the Indonesian criminal justice system, every public prosecutor possesses the authority to cease criminal prosecution in the name of public interest. In contrast, in the Netherland, only the Attorney General (Procureur Generaal) at the Supreme Court has this authority. This article discusses this authority to cease of terminate criminal prosecution in the name of public interest. To do this a comparative approach is used in which the ruling of this authority to terminate criminal prosecution as found in the Draft of the Indonesian Criminal Code will be compared against the same regulation and policy used in the Netherlands. A doctrinal and comparative law approach will be used. One recommendation resulting from this research is the need to re-evaluate the existing procedure and requirement of terminating criminal prosecution in the public interest in the Indonesian context and the introduction of Rechter-Commissaris into the criminal justice system.